2017
DOI: 10.1021/acs.chemmater.6b03808
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ln2Ti2O7 Layered Perovskites: A Survey of the Anionic Lattice, Electronic Features, and Potentials

Abstract: The reduction of the layered perovskites Ln 2 Ti 2 O 7 (LnTO, with lanthanide Ln= La, Pr, Nd) was studied with the aim to shift the UV photocalytic activity for water splitting in the visible range by Ti 3+ donor doping. For all phases, after reduction by CaH , the absorbance is extended beyond the UV-vis region, giving rise to a gap-like edge in the mid-infrared at ~0.4eV with a dark coloration of the samples. When the precursor with Ln= La was reduced under high temperature H 2 flow, we found a progressive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…The interreticular distances d 00l coincide with the reference data JCPDS #33-0942 corresponding to the Nd 2 Ti 2 O 7 monoclinic [28,29]. It has been reported that Nd 2 Ti 2 O 7 has a thermodynamically stable stratified perovskite structure [30]. Figure 4 shows the FT-IR spectrum of the Nd 2 Ti 2 O 7 nanoparticles.…”
Section: Resultssupporting
confidence: 73%
“…The interreticular distances d 00l coincide with the reference data JCPDS #33-0942 corresponding to the Nd 2 Ti 2 O 7 monoclinic [28,29]. It has been reported that Nd 2 Ti 2 O 7 has a thermodynamically stable stratified perovskite structure [30]. Figure 4 shows the FT-IR spectrum of the Nd 2 Ti 2 O 7 nanoparticles.…”
Section: Resultssupporting
confidence: 73%
“…It is observed that the inert basal planes are activated due to the introduction of selenium vacancies, which provide the active sites for hydrogen adsorption to enhance the HER. Similar work of using reductive annealing has also been reported for the effective creation of oxygen vacancies in CaMnO 3 and Ln 2 Ti 2 O 7 perovskites …”
Section: Engineering Of Functional Vacanciesmentioning
confidence: 99%
“…We further note that it is not yet possible to predict whether an oxygen-deficient product or oxyhydride product will result; for example, an anatase TiO 2 film simply gives a dark-colored TiO 2– x phase when treated with CaH 2 [ 36 ], whereas BaTiO 3 gives the oxyhydride. La 2 Ti 2 O 7 contains only minute amounts of hydride [ 37 ].…”
Section: Synthesis Of Oxyhydridesmentioning
confidence: 99%